Business Analysis Of Automatic Photobooth Business At Slay The Box Using Business Model Canvas In Bandar Lampung City - Sultan Alfats Napitupulu; Rr. Erlina (International Journal of Economics, Business and Innovation Research, 2024)
Intense business development between Slay The Box and its competitors requires management to work professionally and have a deep understanding of their business for evaluation and establishment of competitive strategies. This research aims to design a new business model as a business development strategy at Slay The Box using the business model canvas approach. The research uses a qualitative method by conducting interviews with related parties, then analyzed using SWOT to determine the Business Model Canvas to be applied. The results showed that the current business model description of Slay The Box is at the development and maintenance stage which can be seen from the aspects of the Business Model Canvas analyzed by SWOT. The results of the SWOT analysis, Slay The Box must be better able to read market movements and booth locations to maximize the business that is already running. Maintaining product value, creating relationships with customers, and innovating to maintain the company's good image.